Adsorption Studies of Phenols in Aqueous Solution Using Activated Carbon Prepared From Several Part of Oil Palm Tree - Abu Bakar, Norlaili (1999)
The activated carbon used in the adsorption of phenols were prepared from oil palm trunk, shell and empty fruit bunches. A commercial activated carbon obtained from a local manufacturer (KI 5060) was used as comparison. The study was carried out to investigate several factors affecting the extent of phenol adsorption. The study was divided into two parts. The first part was the characterization of the activated carbon including surface area and porosity analysis, determination of iodine number, ash content, trace elements, infrared analysis and the morphology of activated carbon. The second part dealt with the adsorption of phenol and its derivatives onto the activated carbon. The study included investigation of the effects of initial concentration, types of activated carbon particles (chips or powder), surface area, pH solution, and types of substituent groups on adsorption. The higher uptake was achieved in higher concentrations of phenol, but the percentage removal gave the opposite result. The higher uptake was also obtained with higher surface area (15-CP) than low surface area due to more vacant area that need to be occupied. The adsorption of phenol was constant with low pH solutions and decreased with high pH solutions. Oil palm trunk gave better adsorption than oil palm shell or empty fruit bunches. The substituent group of benzene rings of phenol play an important role in adsorption. The electron withdrawal group (N02 and CI) enhanced the adsorption; whereas the electron-donating group (CH3) gave the opposite reaction. The adsorption data were tested for Freundlich and Langmuir isotherms. In addition, the Brunner, Emmet and Teller (BET) isotherm was also tested. Phenol and o-nitrophenol followed all adsorption isotherm (Langmuir, Freundlich and BET), but o-chlorophenol, m-chlorophenol, pchlorophenol, m-cresol and p-cresol were only valid for Freundlich and BET isotherm.